The first ornithocheiromorph humerus from Wuerho (Urho), China, with a new isotopic age of the Tugulu Group - JUNYI SONG; YUTING ZHONG; SHUNXING JIANG; XIAOLIN WANG (Anais da Academia Brasileira de Ciências)
Abstract Pterosaur remains are rare from the lowermost Cretaceous, hampering our understanding of the taxonomic and morphological diversities of pterosaurs during this period. The Lower Cretaceous Tugulu Group in Wuerho, China is renowned for hosting the Wuerho Pterosaurian Fauna (WPF), which has so far yielded numerous fossil remains of two dsungaripterid pterosaurs, Dsungaripterus weii and Noripterus complicidens. Here we report a partial ornithocheiromorph humerus from the WPF, representing a deeply divergent clade from Dsungaripteridae. The scarcity of ornithocheiromorphs from the WPF might be interpreted by niche partitioning with dsungaripterids. Meanwhile, we also report a U-Pb zircon age of 134.27 ± 0.36 Ma dated by LA-ICP-MS for the tuffaceous layer at the uppermost part of the Shengjinkou Formation, confirming the Valanginian age of the WPF presented by a previous study. The Wuerho region is one of the few localities producing abundant pterosaur fossils and the only one with an earliest Cretaceous age. The new finding here also suggests that Ornithocheiromorpha had rapidly diversified and achieved a global distribution during the earliest Cretaceous, presumably through a series of modifications on the locomotor apparatus including the warped deltopectoral crest of the humerus, which might substantially improve their flight efficiency.